A Dimeric η1, η5‐Germole Dianion Bridged Titanium(III) Complex with a Multicenter Ti−Ge−Ge−Ti Bond. (12th June 2018) - Dong, Zhaowen; Janka, Oliver; Kösters, Jutta; Schmidtmann, Marc; Müller, Thomas
Abstract: Dimeric germole dianion bridged Ti III and Zr IV complexes have been synthesized. In these complexes, the germole dianion adopts a formal η 1, η 5 coordination to the two metal centers. The bonding situation in these bridged dimers is dominated by a covalent Ge−Ge interaction that results, for example, in a strong antiferromagnetic coupling of the d 1 Ti centers. Abstract : Die vielfältigen Koordinationsmuster aromatischer Germol‐Dianionen wurden durch die Synthese dimerer Ti III ‐ und Zr IV ‐Komplexe belegt. Rechnerische Analysen offenbarten eine unerwartete kovalente Ge‐Ge‐Wechselwirkung, die die Eigenschaften dieser Komplexe beeinflusst.